HUBUNGAN DUKUNGAN KELUARGA DENGAN POLA DIET PASIEN HIPERTENSI - Nisfil Mufidah; Rahmad Wahyudi; Khodaifi Khodaifi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hypertension is a global public health problem that triggers heart disease, kidney failure, stroke is a disease characterized by an increase in blood pressure, premature death and disability. The problem that occurs in hypertensive patients in the Batulenger Puskemas Work Area is the high number of hypertension sufferers. This study aims to analyze the relationship between Family Support and Dietary Patterns of Hypertensive Patients. The research design uses descriptive analytics with a correlational design that examines the relationship between variables. Using a cross sectional approach The independent variables of this study are family support and dietary pattern depeden variables. The population of 55 hypertensive patients in the working area of the Pakong Health Center with a sample of 48 with sampling techniques using Non Probability with purposive sampling techniques. Data collection techniques using questionnaires. Statistical test using spearman rank test with (a=0.05). The results showed that the value of the results of fassic activity showed that half of the family support showed enough for 17 (35%) respondents. The diet pattern mostly showed enough 25 respondents (52%). Based on the statistical spearman rank test with the value (p=0.034) < (a=0.05). So it can be concluded that there is a relationship between Family Support and Dietary Patterns of Hypertensive Patients It is recommended for the elderly to provide support from the family to prevent hypertension and strive to manage the diet properly and correctly.